The Effect of Inquiry Model in Learning Islamic Religious in Senior High School - Azizah, Aqila; Asni, Nabila Zahratul; Yusfiansyah, Syafwan; Gusmaneli, Gusmaneli (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2024)
This research is based on the rapid development of schools in the modern era, where each school continues to innovate in learning methods so that students remain motivated and do not feel bored in the classroom. Boredom and boredom are one of the inhibiting factors in the teaching and learning process. So that teachers must have creativity in delivering learning materials. This study aims to analyze the effect of the inquiry model in learning Islamic religious education at the senior high school level in Indonesia. This research uses a qualitative method with a content analysis approach. The data sources in this study are thirty articles that have been published in several accredited journals. The results of this inquiry learning model can have a positive effect on students, namely students become more active in learning Islamic religious education, students can solve problems by discussing and improving students' thinking skills. To improve students' ability to think critically and seek information and solve problems. The inquiry model can increase students' interest in learning because it allows them to actively participate in the learning process. This research can be used as initial information for teachers in determining learning models or strategies.